2023
DOI: 10.1038/s41598-023-31652-2
|View full text |Cite
|
Sign up to set email alerts
|

Optical investigation and computational modelling of BaTiO3 for optoelectronic devices applications

Abstract: ABX3 perovskite-based materials have attracted research attention in various electronic and optoelectronic applications. The ability to tune the energy band gap through various dopants makes perovskites a potential candidate in many implementations. Among various perovskite materials, BaTiO3 has shown great applicability as a robust UV absorber with an energy band gap of around 3.2 eV. Herein, we provide a new sonochemical-assisted solid-phase method for preparing BaTiO3 thin films that optoelectronic devices … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 68 publications
(97 reference statements)
1
7
0
Order By: Relevance
“…1 exhibit prominent characteristic sharp peaks of barium titanate only, suggesting that the barium titanate nanoparticles possess a pure crystalline structure, as clarified from JCPDS No. 01-089-1428 [ 57 ]. The obtained diffraction peaks at 2 θ = 66.24°, 56.50°, 51.27°, 45.39°, 39.15°, 31.89°, and 22.44° were ascribed to the (220), (211), (210), (200), (111), (110), and (100) miller planes of BaTiO 3 nanoparticles, respectively, as clarified from JCPDS No.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 exhibit prominent characteristic sharp peaks of barium titanate only, suggesting that the barium titanate nanoparticles possess a pure crystalline structure, as clarified from JCPDS No. 01-089-1428 [ 57 ]. The obtained diffraction peaks at 2 θ = 66.24°, 56.50°, 51.27°, 45.39°, 39.15°, 31.89°, and 22.44° were ascribed to the (220), (211), (210), (200), (111), (110), and (100) miller planes of BaTiO 3 nanoparticles, respectively, as clarified from JCPDS No.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained diffraction peaks at 2 θ = 66.24°, 56.50°, 51.27°, 45.39°, 39.15°, 31.89°, and 22.44° were ascribed to the (220), (211), (210), (200), (111), (110), and (100) miller planes of BaTiO 3 nanoparticles, respectively, as clarified from JCPDS No. 01-089-1428 [ 57 ]. The mean crystallite size, which was determined using the Scherrer equation [ 58 , 59 ], of the EA600 and EA800 samples is 14.83 and 22.27 nm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Though, BTO has a good piezoelectricity and has been widely studied, it always requires high energy stimulus (bandgap of 3.19 eV) [37] . On the other hand, BiFeO 3 , another perovskite‐type piezoelectric material, though its piezoelectricity is lower, has a narrow bandgap (~2.2 eV), and a misaligned conduction band with a redox potential of 0.33 V vs. RHE [38] .…”
Section: Flexible Composite Systemsmentioning
confidence: 99%
“…Though, BTO has a good piezoelectricity and has been widely studied, it always requires high energy stimulus (bandgap of 3.19 eV). [37] On the other hand, BiFeO 3 , another perovskite-type piezoelectric material, though its piezoelectricity is lower, has a narrow bandgap (~2.2 eV), and a misaligned conduction band with a redox potential of 0.33 V vs. RHE. [38] Therefore, the combination of BiFeO 3 and BTO may give reasonable piezoelectricity and narrower bandgap, and appropriate redox potential for electron-hole pair generation.…”
Section: Perovskites-pvdfmentioning
confidence: 99%
“…At high temperatures, i.e., above 400 K, BT possesses the centrosymmetric cubic structure with A at the corners, B at the center, and the oxygens at the face centers of a cube. , However, with decrease in the temperature, the structure transforms through successive phase transitions to three different ferroelectric phases, each involving small distortions from the cubic symmetry. , At 398 K, it undergoes a paraelectric to ferroelectric transition in to a tetragonal structure , and has an orthorhombic structure between 278 K and 183 K and, finally, it possesses a rhombohedral structure , below 183 K. Such samples are known to have a great applicability, due to its excellent piezoelectric and ferroelectric properties, such as in actuators, capacitors, electro-mechanical transducers, infrared sensors, and memory devices . Moreover, BT is also used as an optical modulator due to its nonlinear optical properties and in photovoltaic devices as a light absorbing material due to its suitable bandgap for absorbing violet and UV solar radiation and can enhance the performance of solar cells by improving charge separation (due to larger dielectric constant) and transport properties. , Furthermore, Sati et al have explored temperature-dependent dielectric loss, which decreases in cubic phase due to strong eph interaction . Jiaji et al demonstrated a large modulation of electron–phonon coupling by utilizing soft polar phonons and an emergent superconducting “dome” in n-doped BT .…”
Section: Introductionmentioning
confidence: 99%